Upaya Meningkatkan Pemahaman dan Hasil Belajar Matematika Peserta Didik Melalui Model Pembelajaran Discovery Learning di Kelas II SDN 57/X Kampung Laut Semester Ganjil Tahun Ajaran 2021/2022 - Fauziah Fauziah (Journal on Education, 2022)
This study aims to describe and obtain information on improving Mathematics learning outcomes through Discovery Learning. This research is classroom action research consisting of two cycles, each cycle consisting of two meetings. Each meeting consists of four stages, namely planning, implementation, observation, and reflection. The subjects of this study were the seconds’ grade students of SDN 57/X Kampung Laut, totaling 27 people. This research was conducted in the odd semester of the 2020/2021 academic year. Data collection techniques using tests, observations, and documentation. Data were analyzed using percentages. The results showed that through Discovery Learning can improve the mathematics learning outcomes of second grade students at SDN 57/X Kampung Laut by giving praise